Information System Strategic Planning Based On Togaf Adm Framework In Budget, Treasury, And Accounting Function Of Revenue And Financial Management Department Bandung Regency - Almareta Harasti Nuraini; Yuli Adam Prasetyo; Ridha Hanafi (eProceedings of Engineering, 2016)
Abstract Revenue and Financial Management Department (DPPK), a part of Bandung Regency Government, is a public oriented enterprise that engaged in financial world. DPPK needs to improve their information technology (IT) usage for upgrading Indonesia e-Government Ranking. For carrying out IT usage, DPPK needs information system strategic planning that is supported by enterprise architecture (EA) concept. By designing enterprise architecture using TOGAF ADM framework, DPPK has long-term information system strategic planning that align with its business strategy. This result can be useful to optimize IT resource that support business activities, in order to achieve goal and objective based on the vision and mission of DPPK. Keywords: information system strategic planning, enterprise architecture, TOGAF ADM